2019
DOI: 10.3390/met9091008
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High Strength Mg-9Li Alloy via Multi-Pass ECAP and Post-Rolling

Abstract: In this study, a high-strength Mg-9Li alloy was developed via multi-pass equal-channel-angular-pressing (ECAP) and post rolling, of which the yield tensile stress (YTS) and ultimate tensile stress (UTS) were 166 MPa and 174 MPa representing about 219% and 70% increase in YTS and UTS respectively, compared to the cast alloy. The cast alloy was ECAP processed at 200 °C for 4, 8, and 16 passes, followed by room-temperature rolling to a total thickness reduction of 50%. The 8-passes ECAPed (E8) alloy presented the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…Meanwhile, the increasing dislocation density and structure refinement can improve the microhardness of HPTed materials. Figure 8 shows the advantages of the HPT process in the YS and ductility of different metals (Qu et al, 2009;Kapoor et al, 2010;Liu et al, 2013;Toroghinejad et al, 2013;Bazarnik et al, 2016;Zou et al, 2016;Su et al, 2018;Klu et al, 2019;Klu et al, 2022). It can be seen that the HPTed Cu-16Al alloys shows an increase of 80 MPa in YS compared with the ECAPed alloys.…”
Section: Improving Microhardness/strength and Ductilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, the increasing dislocation density and structure refinement can improve the microhardness of HPTed materials. Figure 8 shows the advantages of the HPT process in the YS and ductility of different metals (Qu et al, 2009;Kapoor et al, 2010;Liu et al, 2013;Toroghinejad et al, 2013;Bazarnik et al, 2016;Zou et al, 2016;Su et al, 2018;Klu et al, 2019;Klu et al, 2022). It can be seen that the HPTed Cu-16Al alloys shows an increase of 80 MPa in YS compared with the ECAPed alloys.…”
Section: Improving Microhardness/strength and Ductilitymentioning
confidence: 98%
“…Table 3 summarizes the mechanical properties of metals produced by SPD processes (Iwahashi et al, 1998;Munnoz-Morris et al, 2003;Peng et al, 2007;Qu et al, 2009;Kapoor et al, 2010;Kawasaki et al, 2011;Zhang et al, 2011;Popov et al, 2012b;Liu et al, 2013;Toroghinejad et al, 2013;Kawasaki et al, 2014b;Huang et al, 2014;Meng et al, 2014;Lu et al, 2015;Bazarnik et al, 2016;Zou et al, 2016;Tang et al, 2017;Čížek et al, 2017;Gu et al, 2018;Su et al, 2018;Klu et al, 2019;Xue et al, 2019;Klu et al, 2022;Öğüt et al, 2022). It can be seen that HPT processing has obvious advantages in processing metals with high strength and microhardness in comparison with other thermomechanical processing methods, such as ECAP, ARB, extrusion, and rolling.…”
Section: Improving Microhardness/strength and Ductilitymentioning
confidence: 99%
“…Thirteen research papers have been published in this Special Issue of Metals. The papers cover a wide spectrum of topics, including (i) deformation mechanisms, the mechanical properties and fatigue behaviour of SPD-processed materials [1][2][3][4][5][6][7], (ii) microstructural and mechanical stability at elevated temperatures [8,9], phase formations in alloys [10], the improvement of physical properties (electrical conductivity [11], magneto-resistance [12]) and biomedical properties (biocorrosion resistance [6], biocompatibility [13]) by SPD.…”
Section: Contributionsmentioning
confidence: 99%
“…In the thematic area (i), Klu et al [1] investigated a combination of multi-pass warm ECAP followed by rolling at room temperature for the development of a high-strength Mg-9Li duplex alloy and carried out a systematic investigation of the microstructure-mechanical properties relationship. They found that grain boundary strengthening and dislocation strengthening are the main factors determining the strength of this alloy.…”
Section: Contributionsmentioning
confidence: 99%
“…The cast billets, with size of 20 × 20 × 45 mm 3 , were cut from the cast ingot and processed by multi-pass ECAP to achieve dramatic grain refinement. Rotary-die (RD) ECAP technology was applied, the processing principles of which have been detailed in our previous works [37][38][39][40]. Graphite slurry was applied to the billets and mold channels to reduce friction during ECAP processing.…”
Section: Processing Routementioning
confidence: 99%